2006
DOI: 10.1080/15459620600584295
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Prevention—Occupational Safety and Health in Hospitals: Alternatives and Interventions

Abstract: An integrated pollution prevention (P(2)) and occupational safety and health (OSH) worksite intervention and alternatives assessment strategy was developed in hospitals. It was called the Pollution Prevention-Occupational Safety and Health (P(2)OSH) assessment for the "Sustainable Hospitals Project." Methods included (a) developing a participatory intervention model for introducing more environmentally sound, healthy, and safe materials and work practices for specific hospital procedures; (b) developing an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
2
14
0
3
Order By: Relevance
“…Os trabalhadores da saúde estão expostos a poluição ambiental (15) , mas mesmo com orientações como não utilizar campos apenas de algodão e sim mesclados commicrofibra e não fazer uso do mercúrio nas unidades de saúde, estas interferências não são relevantes para a diminuição da poluição ambiental.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Os trabalhadores da saúde estão expostos a poluição ambiental (15) , mas mesmo com orientações como não utilizar campos apenas de algodão e sim mesclados commicrofibra e não fazer uso do mercúrio nas unidades de saúde, estas interferências não são relevantes para a diminuição da poluição ambiental.…”
Section: Discussionunclassified
“…Também identificou-se que os trabalhadores de enfermagem estão submetidos à poluição ambiental (15) . Os trabalhadores também podem apresentar dermatites nas mãos por fazerem uso de luvas para a realização de procedimentos.…”
Section: Dois Estudosunclassified
See 1 more Smart Citation
“…A large study of pollution prevention activities in the hospital industry concluded that legal standards remain important incentives for hospitals to reduce or eliminate hazards. (38) A crucial strategy for implementing safer lithographic cleanup products will be to bring regulations in other air districts up to the standards of the SCAQMD. The opportunity to address these challenges exists.…”
Section: Linkages Between Occupational and Environmental Healthmentioning
confidence: 99%
“…They have courses that target the full life cycle of a process or product so that occupational safety and health concepts are considered in depth during the design and manufacturing phase as well as when the process or product is introduced into the work place. And they recently Environmental Health Risk V 191 published a study on how to implement more environmentally-sound, healthier and safer design alternatives in health care [8].…”
Section: Educationmentioning
confidence: 99%